Comparative Relevance of Physical Fitness and Adiposity on Life Expectancy: A UK Biobank Observational Study - Zaccardi, Francesco; Davies, Melanie J; Khunti, Kamlesh; Yates, Tom (Mayo Clinic proceedings, 2019)
To investigate the extent to which 2 measures of physical fitness-walking pace and handgrip strength-are associated with life expectancy across different levels of adiposity, as the relative importance of physical fitness and adiposity on health outcomes is still debated. Usual walking pace (self-defined as slow, steady/average, brisk), dynamometer-assessed handgrip strength, body mass index (BMI), waist circumference, and body-fat percentage determined at baseline in the UK Biobank prospective cohort study (March 13, 2006, to January 31, 2016). Life expectancy was estimated at 45 years of age. The median age and BMI of the 474,919 participants included in this analysis were 58.2 years and 26.7 kg/m , respectively; over a median follow-up of 6.97 years, 12,823 deaths occurred. Participants reporting brisk walking pace had longer life expectancies across all levels of BMIs, ranging from 86.7 to 87.8 years in women and 85.2 to 86.8 years in men. Conversely, subjects reporting slow walking pace had shorter life expectancies, being the lowest observed in slow walkers with a BMI less than 20 kg/m (women: 72.4 years; men: 64.8 years). Smaller, less consistent differences in life expectancy were observed between participants with high and low handgrip strength, particularly in women. The same pattern of results was observed for waist circumference or body-fat percentage. Brisk walkers were found to have longer life expectancies, which was constant across different levels and indices of adiposity. These findings could help clarify the relative importance of physical fitness and adiposity on mortality.